Upaya Peningkatan Kapasitas Mahasiswa Keperawatan dalam Menghadapi Pandemi COVID-19 - Ika Nur Pratiwi; Herley Windo Setiawan; Lailatun Nimah; Rista Fauzinigtyas; Zulfayandi Pawanis (Abimanyu : Jornal of Community Engagement, 2020)
The Covid-19 pandemic made health workers at the forefront must provide direct treatment to patients and take efforts to prevent the spread of the disease. The impact of the pandemic in the education is made all higher education institutions in all zones to provide online learning. Developing online learning for nursing students needs strategies because the competencies had achieved involve cognitive, affective and psychomotor domains. The purpose of community service (PKM) is to provide education about Covid-19 as an effort to increase the capacity of nursing students in the face of the COVID-19 pandemic. The PKM method uses the Community Based Research (CBR) approach through education about the latest management of Covid-19, nursing care for Covid-19 patients and alertness based on transmission of COVID-19 (Transmition based Precaution). The final evaluation of the PKM program by comparing the pre-test and post-test scores on knowledge. PKM results, there were 178 participants with an average age of 22 years and the majority of them were women (104 participants). The measurement results for the level of knowledge p = 0.000 (p <0.05) so that there is a significant difference in the level of knowledge between before and after being given education. Community service activities include increasing knowledge and understanding of nursing students in dealing with Covid-19 in a clinical setting. So, after students graduate and then work, they can quickly adapt to the work environment in breaking the chain of health problems that occur.